Karyotypes of four species of Xenodontini snakes (Serpentes) and implications for taxonomy - Falcione, Ana Camila (2016)
The karyotypes of four South American Xenodontini snake species, Lygophis dilepis, L. meridionalis, L. flavifrenatus and L. anomalus, are here described for the first time. We studied specimens from northeastern Argentina using conventional and silver (Ag-NOR) staining. While the typical ophidian karyotype is 2n= 36, we found that the karyotype of the studied species is 2n=34, with metacentric and submetacentric chromosome pairs. The Ag-NOR staining revealed that nucleolar organizer regions (NORs) are located on one pair of microchromosomes. In L. dilepisand L. anomalus the 4th chromosome pair is heteromorphic, and we suggest that it might be considered as the ZW sex chromosome pair. The optimization of available karyological data on a molecular phylogenetic tree of the tribe Xenodontini shows that the diploid numbers of the three genera (2n= 28, 30 and 34) represent putative synapomorphies for Erythrolamprus, Xenodon and Lygophis, respectively. Our results provide new insights which fill gaps in our knowledge on the cytology in the genus Lygophis and identified a possible diagnostic character for the genus.